Antiferromagnetic Inverse Spinel Oxide LiCoVO4 with Spin‐Polarized Channels for Water Oxidation. Issue 10 (31st January 2020) - Chen, Riccardo Ruixi; Sun, Yuanmiao; Ong, Samuel Jun Hoong; Xi, Shibo; Du, Yonghua; Liu, Chuntai; Lev, Ovadia; Xu, Zhichuan J.
Abstract: Exploring highly efficient catalysts for the oxygen evolution reaction (OER) is essential for water electrolysis. Cost‐effective transition‐metal oxides with reasonable activity are raising attention. Recently, OER reactants' and products' differing spin configurations have been thought to cause slow reaction kinetics. Catalysts with magnetically polarized channels could selectively remove electrons with opposite magnetic moment and conserve overall spin during OER, enhancing triplet state oxygen molecule evolution. Herein, antiferromagnetic inverse spinel oxide LiCoVO4 is found to contain d 7 Co 2+ ions that can be stabilized under active octahedral sites, possessing high spin states S = 3/2 ( t 2g 5 e g 2 ). With high spin configuration, each Co 2+ ion has an ideal magnetic moment of 3 µ B, allowing the edge‐shared Co 2+ octahedra in spinel to be magnetically polarized. Density functional theory simulation results show that the layered antiferromagnetic LiCoVO4 studied contains magnetically polarized channels. The average magnetic moment ( µ ave ) per transition‐metal atom in the spin conduction channel is around 2.66 µ B . Such channels are able to enhance the selective removal of spin‐oriented electrons from the reactants during the OER, which facilitates the accumulation of appropriate magnetic moments for triplet oxygen molecule evolution. In addition, the LiCoVO4 reported has been identified as an oxide catalyst with excellent OER activity. Abstract : Antiferromagnetic inverse spinel oxide LiCoVO4 is found to contain spin‐polarized channels. Such channels can enhance selective removal of spin‐oriented electrons from the reactants during the oxygen evolution reaction (OER), which facilitates the accumulation of appropriate magnetic moments for triplet oxygen molecule evolution and conserves the overall spin during the OER.